2014
DOI: 10.1002/art.38780
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cartilage Derived From Murine Induced Pluripotent Stem Cells for Osteoarthritis Drug Screening

Abstract: Objective The discovery of novel disease-modifying drugs for osteoarthritis (OA) is limited by the lack of adequate genetically-defined cartilage tissues for application in high-throughput screening systems. We addressed this need by synthesizing cartilage from induced pluripotent stem cells (iPSCs) to establish and validate an in vitro model of OA. Methods iPSC-derived or native mouse cartilage samples were treated with the cytokine interleukin-1α (IL-1α) for 3 days to model the inflammatory environment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 49 publications
(110 reference statements)
4
60
0
Order By: Relevance
“…No significant effects of IL-1α were found for total collagen or total collagen/DNA (Fig. S1B,C), consistent with previous studies (26) and possibly due to the retention of partially degraded, large macromolecular constituents from enzymatically degraded tissue (18). …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…No significant effects of IL-1α were found for total collagen or total collagen/DNA (Fig. S1B,C), consistent with previous studies (26) and possibly due to the retention of partially degraded, large macromolecular constituents from enzymatically degraded tissue (18). …”
Section: Resultssupporting
confidence: 91%
“…Importantly, cartilage derived from CRISPR/Cas9-edited iPSCs displayed the capacity to withstand treatment with 1 ng/ml IL-1α. Consistent with our work, previous studies have shown that treatment with 1 ng/ml IL-1α results in severe degradation of both engineered cartilage derived from Il1r1-expressing cells as well as cartilage from mouse explants (17, 18, 26). However, in our study, engineered tissue derived from Il1r1 -/- cells was protected from an in vitro model of OA.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, iPSCs can be generated from patients with TRPV4 mutations that cause the spectrum of skeletal dysplasias (Saitta et al, 2014) and the arthopathies, or from patients with osteoporosis, rheumatoid arthritis, or osteoarthritis. Cartilage derived from iPSCs has been shown to replicate various aspects of human disease in vitro (Willard et al, 2014) and can be used to test therapeutic approaches for the spectrum of joint diseases.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Nf-κB). [100] Such findings demonstrate the use of an in vitro arthritis disease modeling platform to identify candidate DMOADs. Future efforts should consider extending this approach to human iPSC-based OA modeling platforms, where human iPSC-derived cartilage tissue might be exposed to OA-relevant stimuli, such as inflammatory cytokines and/or mechanical loading (Key figure, Figure 1).…”
Section: Disease Modeling Applicationsmentioning
confidence: 93%
“…Recent efforts directed towards arthritis disease modeling have shown that administration of inflammatory cytokines IL1 and TNF to engineered tissues derived from murine iPSCs can result in tissue degradation, which is consistent with the detrimental effects of these inflammatory cytokines in the joints of patients harboring various forms of arthritis. [95,100] Degradative changes in induced cartilage might thus be ameliorated through small molecule-mediated inhibition of catabolic enzymes (e.g. Mmp-13) or transcription factors (e.g.…”
Section: Disease Modeling Applicationsmentioning
confidence: 99%